2010
DOI: 10.1093/ndt/gfq413
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery calcification and coronary ischaemia in renal transplant recipients

Abstract: CAC is highly prevalent in renal transplant recipients; it is associated with symptoms of coronary ischaemia. Time on transplantation is an independent determinant of CAC. Future studies to evaluate the prognostic significance of CAC in these patients are necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 38 publications
2
18
1
Order By: Relevance
“…An association between CAC and dialysis vintage has already been demonstrated (Rosas et al 2005). Contrary to Seyahi et al (2011), we found no association between CAC and transplantation duration.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…An association between CAC and dialysis vintage has already been demonstrated (Rosas et al 2005). Contrary to Seyahi et al (2011), we found no association between CAC and transplantation duration.…”
Section: Discussioncontrasting
confidence: 99%
“…As in most other studies examining dialysis (Kraśniak et al 2007) or Tx patients (Rosas et al 2005;Mazzaferro et al 2007;Seyahi et al 2011) CAC significantly correlated with age in both examined groups. In addition, patients from both subgroups with CAC had undergone significantly longer CKD and/or dialysis duration than patients without CAC.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…All papers were observational studies: 11 were prospective, 10 analyzed the prevalence or progression of VC, and 3 studied the impact of VC and vascular outcomes. The prevalence of coronary artery calcification (CAC) in KTRs is higher (61-75%) than that assessed in stage 3 CKD [5,6,7] and lower than that found in hemodialysis patients [8], possibly due to a selection bias of KTRs upon admission to the waiting list. The determinants associated with its presence are: age, dialysis vintage, time on transplantation and high/low turnover bone disease [9].…”
Section: Cardiovascular Disease and Vascular Calcification In Kidney mentioning
confidence: 99%
“…CAC, detected and quantified by CT, affords a reliable linear anatomic estimate of the total plaque burden and is taken clinically as a ‘calcium score'. In the general population, the presence of CAC is associated with symptoms of coronary ischemia and there is a trend towards higher rates of coronary ischemia by scintigraphy in patients with severe CAC [5,58]. In these studies the prevalence of silent myocardial ischemia by scintigraphy was found to be between 10.4 and 46% in patients who had a CAC score >400.…”
Section: Cac Assessmentmentioning
confidence: 99%